2014
DOI: 10.1371/journal.pone.0111539
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-1/ASC Inflammasome-Mediated Activation of IL-1β–ROS–NF-κB Pathway for Control of Trypanosoma cruzi Replication and Survival Is Dispensable in NLRP3−/− Macrophages

Abstract: In this study, we have utilized wild-type (WT), ASC−/−, and NLRP3−/− macrophages and inhibition approaches to investigate the mechanisms of inflammasome activation and their role in Trypanosoma cruzi infection. We also probed human macrophages and analyzed published microarray datasets from human fibroblasts, and endothelial and smooth muscle cells for T. cruzi-induced changes in the expression genes included in the RT Profiler Human Inflammasome arrays. T. cruzi infection elicited a subdued and delayed activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 38 publications
(43 reference statements)
2
44
1
1
Order By: Relevance
“…Because ROS and NO and their by-products are strong cytotoxic agents that may directly kill the pathogen (24) or influence the cellular function by formation of adducts on DNA, proteins, and lipids (25,26), our data suggest that T. cruzi diminishes the oxidative/nitrosative response to ensure its survival in ms. Our finding of inhibition of ROS by DPI (NOX2 inhibitor) and a lack of mitochondrial ROS stimulated by LPS/IFN-␥ (Fig. 2H and I) and our prior T. cruzi infection studies in splenocytes and human THP-1 ms (27,28) suggest that NOX2 is the major source of ROS in ms. How SYL diminishes NOX2 activation to control ROS/NO levels remains to be further investigated. Others have suggested that an elaborate antioxidant network comprising peroxiredoxins that scavenge ROS and NO provides a survival advantage to T. cruzi in immune cells (6).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Because ROS and NO and their by-products are strong cytotoxic agents that may directly kill the pathogen (24) or influence the cellular function by formation of adducts on DNA, proteins, and lipids (25,26), our data suggest that T. cruzi diminishes the oxidative/nitrosative response to ensure its survival in ms. Our finding of inhibition of ROS by DPI (NOX2 inhibitor) and a lack of mitochondrial ROS stimulated by LPS/IFN-␥ (Fig. 2H and I) and our prior T. cruzi infection studies in splenocytes and human THP-1 ms (27,28) suggest that NOX2 is the major source of ROS in ms. How SYL diminishes NOX2 activation to control ROS/NO levels remains to be further investigated. Others have suggested that an elaborate antioxidant network comprising peroxiredoxins that scavenge ROS and NO provides a survival advantage to T. cruzi in immune cells (6).…”
Section: Discussionmentioning
confidence: 54%
“…In the context of T. cruzi, prepared lysates are insufficient to activate an inflammatory response in ms and splenocytes. Human THP-1 ms were shown to lack induction of IL-1␤ with either live T. cruzi and T. cruzi lysate stimulation compared to LPS treatment (28). Splenocytes isolated from normal mice respond to T. cruzi lysates with low levels of production of H 2 O 2 that were enhanced only when splenic cells were primed with live T. cruzi before secondary stimulation with T. cruzi lysate (27).…”
Section: Discussionmentioning
confidence: 97%
“…THP-1 human monocytes (ATCC TIB-202) were suspended in complete RPMI media and incubated at 37°C/5% CO 2 for 24 h in presence of 50 ng/ml phorbol-12-myristate-13-acetate (PMA, Sigma-Aldrich), and then for 48 h in complete RPMI media without any stimulus to generate the resting mφs [21]. RAW 264.7 murine macrophages (ATCC TIB-71) were cultured in high glucose Dulbecco’s modified Eagle’s medium (DMEM) containing 10% fetal bovine serum (Invitrogen, Carlsbad, CA), 2 mmol/l glutamine, 100 IU/ml penicillin, and 100 μg/ml streptomycin (Corning, Corning NY).…”
Section: Methodsmentioning
confidence: 99%
“…El parásito puede influenciar o alterar el comportamiento de estas células a través de la infección directa ( . La activación de estas células presentadoras de antígeno, como los monocitos y macrófagos, tiene que ver con la producción de moléculas efectoras como el óxido nítrico (NO), los productos reactivos del oxígeno (reactive oxygen species, ROS) y las citocinas inflamatorias, las cuales tienen un papel fundamental en la presentación antigénica, así como en la activación subsecuente de la respuesta mediada por linfocitos T. El parásito suele disminuir dicha respuesta alterando la actividad de la enzima NADPH oxidasa, la cual regula la producción de ROS (Dey, et al, 2014). Asimismo, los antígenos derivados del parásito alteran el patrón de citocinas producidas, por ejemplo, las células dendríticas de pacientes con enfermedad de Chagas crónica producen más interleucina 10 (IL-10) que interleucina 12 (IL-12) en presencia de la proteína de choque térmico de T. cruzi.…”
Section: La Respuesta Inmunitaria Innata En Fase Crónicaunclassified